An Overview of Software Defined Environment - Ali Dheyaa Jalil; Abdulkareem A. Kadhim (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Datacenters are a complex environment consisting of network equipment, server hardware and storage systems. The rapid evolution in Information Technology applications and the widely used services and datacenters provided by different vendors make them a big challenge. Traditional datacenters are managed by administrators manually. The growth of datacenters thus reveals problems in managing and controlling. A new technology called Software Defined Environment (SDE) is introduced to solve such problems. SDE solution separates the controlling functions of the datacenters from its physical components and performs such operations in a centralized controller. The present work introduces an overview of SDE and its features to solve common problems in datacenters such as the controlling problems and the management problems in adding an extra physical hardware. Suitable scenarios are suggested with the assistance of Software Defined Network (SDN) and its useful features. Possible tools and resources to implement SDE are also presented.